I just want to be somebody: Exploring students’ motivations and experiences in universities - Gyamera, G.O. (South African Journal of Higher Education, 2018)
There is burgeoning literature on the challenges confronting many Sub Saharan African universities. Such challenges have worsened in the present neoliberal context of the universities. This paper draws on a qualitative data in three public universities in Ghana to discuss students’ motivations in going to the universities and their experiences in the institutions. It discusses how students perceive and deal with the institutional challenges they are confronted with. Whilst the various challenges cannot be ignored, it appears many of the students have adopted ‘adaptive preferences’ to deal with their challenges and sustain their motivations. I argue for the universities to strive to boost student services not only academically but socially including leisure and networking activities. Also, in the neoliberal context of the universities, I suggest the universities to encourage the intrinsic value of knowledge other than its instrumental usage.